DOCUMENT CHECK AT BORDER CONTROL AS A BASIC ELEMENT OF INTERNAL SECURITY IN THE REPUBLIC OF LATVIA - Sporans, Davis; Volkova, Jelena; Ignatjevs, Olegs (Border Security and Management, 2023)
The aim of the current research is to make extensive study of the document check process, to examine it’s legal and practical matters within the State Border Guard of Latvia and to define necessary actions to develop the process mentioned above. To achieve the aim, following objectives were defined: to study the legal matters of the document check process in State Border Guard, to evaluate State Border Guard’s technical means in the field of document check, to study practical aspects in document check process according to data collected from respondents within State Border Guard, to analyze the problematics of the document check process in State Border Guard and to define the necessary development decisions. Following research methods were used: monographic or descriptive method, document analysis, logic- constructive method, analytic method, sociological survey method. Within the topic of Document check at border control as a basic element of internal security in the Republic of Latvia, the authors thoroughly examined the process of document check, its legal and practical aspects within the example of State Border Guard of Latvia and also defined necessary development actions in the period between years 2017 and November 2021.